Kebijakan Sanksi Administrasi BPHTB Untuk Pemberian Hak Baru Atas Tanah di Provinsi DKI Jakarta Dalam Perspektif Collaborative Governance - Dominicus Donny Pamungkas (Jurnal Manajemen Pelayanan Publik, 2018)
The large number of land in DKI Jakarta province that have not yet beenregistered is a significant potential tax in increasing BPHTB tax revenue. But in its implementation, the imposition of BPHTB tax for granting new rights to this land is still experiencing obstacles. The constraints experienced are the imposition of BPHTB administrative sanctions based on the time of debt due to the signing of the BPN Decree (SK). In this case, Jakarta’s citizenas tax payers felt disadvantaged because they were subjected to administrative sanctions due to the delay in receiving the BPN Decree. Based on the results of the analysis through data collection in the field, literature study as reference material and in-depth interviews with related parties, author concluded that BPRD DKI Jakarta, DKI Jakarta Regional Office of BPN and PPAT DKI Jakarta have been cooperating well in the imposition process of BPHTB tax. But in reality, there are still problems in the case of the imposition of BPHTB administrative sanctions for granting new rights to land due to delays in receipt of SK BPN by taxpayers. To minimize this, a more comprehensive collaboration is needed between agencies, namely BPRD DKI Jakarta, Regional Office of BPN DKI Jakarta and PPAT in DKI Jakarta by conducting Collaborative Governance. With Collaborative Governance, it is expected that services to taxpayers will be better and BPHTB tax revenues in DKI Jakarta will increase.